A Role of Herbal Formulationin the management of Diabetes mellitus (Madhumeha)- A Review Article - Suman, Deepak; Jaiman, Devesh (International Research Journal of Ayurveda & Yoga, 2024)
Diabetes mellitus is a growing health hazard in developing countries.As a psychosomatic disease and due to most dangerous complications, DM has grabbed the attention of health community all over the world.Diabetes mellitus (DM) is a clinical syndrome characterized by hyperglycaemia due to absolute or relative deficiency of insulin.According to A etiological factor, pathogenesis and clinical features Diabetes mellitus correlated with Madhumeha in Ayurveda.Madhumehi patients pass sweet urine in addition to excessive urine. Intake of Guru, Snigdha, Picchhila substances, intake of new grains, meat of Anupa and Jalchara animals, milk and milk products, jaggery and its products, flour, lack of exercises, sedentary life style are the causes of Madhumeha.Even the genetic basis of the disease has been highlighted in the Ayurveda. Similarly,Modern science also recognizes that sedentary lifestyle, Obesity and genetic factors also play an important role in its development. So due to lack of effective medicine,wide spectrum of disease, need of time is to go for cost effective, safe and efficient treatment of Madhumeha.Keeping all above points in mind aherbal formulationhas beenselected to know the effect in treating Madhumeha(DiabetesMellitus).Harbal formulation contents are Gurmaara, Amalaki, Vijayasara, Karela, Guduchi, Neema, Jamuna, Methi, andChirayata.